Immunohistochemical study of gastrointestinal endocrine cells in the porcupine (Hystrix cristata) - Yaman, M.; Tarakci, B. Gencer; Bayrakdar, A.; Atalar, O.; Dabak, O. (Ecole Nationale Veterinaire Toulouse, 2007)
The regional distribution and the relative frequency of endocrine cells was studied immunohistochemically in the gastrointestinal tract of the porcupine (Hystrix cristata), using antiserum against serotonin, calcitonin gene related peptide (CGRP), somatostatin-14, neurotensin, cholecystokinin (CCK) and vasoactive intestinal polypeptide (VIP). Scrotonin immunoreactive cells were observed in all regions of the gastrointestinal tract and they were particularly abundant in the stomach and the duodenum, whereas the presence of somatostatin 14 positive cells and of neurotensin positive cells were restricted to intestines (to small and large bowels and only to small intestine, respectively) and CGRP immunoreactive cells were predominantly evidenced in the stomach. By contrast, CCK and VIP immunoreactive cells were not detected in the porcupine.
Keywords: immunohistochemistry; porcupine; calcitonin gene related peptide; somatostatin-14; neurotensin; cholecystokinin; vasoactive intestinal polypeptide